Assessment of chemotherapy resistance changes in human colorectal cancer xenografts in rats based on MRI histogram features - Wu, Min-Yi; Han, Qi-Jia; Ai, Zhu; Liang, Yu-Ying; Yan, Hao-Wen; Xie, Qi; Xiang, Zhi-Ming (Frontiers in Oncology, 2024)
We investigated the value of MRI Histogram features, a non-invasive method, in assessing the changes in chemoresistance of colorectal cancer xenografts in rats.Methods: A total of 50 tumor-bearing mice with colorectal cancer were randomly divided into 2 groups: control group and 5-Fu group. The MRI Histogram characteristics and the expression levels of p53 protein and MRP1 were obtained at 24h, 48h, 72h, 120h and 168h after treatment. Results: Sixty highly repeatable MRI histogram features were obtained.There were 16 MRI histogram parameters and MRP1 resistance protein differences between groups. 24h after treatment, the MRI histogram texture parameters of T2WI images (10%, 90%, Median, Energy, Root-Mean-Squared) and D images (10%, Rang) were positively correlated with MRP1 (r=0.925, p=0.005). 48h after treatment, histogram texture parameters of ADC images (Energy) were positively correlated with the presence of MRP1 resistant protein (r=0.900, p=0.037). There was no statistically significant difference between MRI histogram features and p53 protein expression level.Conclusions: MRI Histogram texture parameters based on T2WI, D and ADC maps can help to predict the change of 5-FU resistance in colorectal cancer in the early stage and provide important reference significance for clinical treatment.